Clinical features and treatment outcomes of Vibrio vulnificus infection in the coastal city of Ningbo, China - Wang, Jieyi; Weng, Xingbei; Weng, Yuesong; Xu, Quanjun; Lu, Yao; Mo, Yijun (Frontiers in Microbiology, 2023)
Background: Vibrio vulnificus is a gram-negative, opportunistic pathogen common to warm waters worldwide. Human V. vulnificus infection is rare and typically affects those residing in coastal areas during the summer months, but it causes rapid deterioration and is fatal.The medical records of six patients with sepsis caused by V. vulnificus infection who were treated at the First Affiliated Hospital of Ningbo University from 2020 to 2022 were retrospectively reviewed. The patient demographics, clinical symptoms, laboratory test results, treatments, and outcomes are summarized.Results: V. vulnificus infection was confirmed by blood or pus culture, 16S ribosomal DNA sequencing, and metagenomic next-generation sequencing. All six patients were male with preexisting liver diseases and two reported consuming seafood before the onset of symptoms. Of the six patients, four succumbed to the disease, two recovered, and one underwent leg amputation.Conclusions: V. vulnificus infection progresses rapidly and is highly fatal, thus prompt and aggressive treatment is necessary. V. vulnificus infection should be considered in older (>40 years) patients with a history of liver disease and recent consumption of seafood or exposure to seawater, especially those residing in coastal areas during the summer months.